Variation of herbivory damage on potato (Solanum tuberosum ssp. andigena) leaves in different degrees of proximity to native vegetation in Combaya, La Paz - Emili Antonia Jiménez (Journal of the Selva Andina Biosphere)
High herbivory rates are related to the emergence of new pests and are a problem for plants of commercial interest, such as potato (Solanum tuberosum). While the interest of farmers is to know the main tuber predators, it is also necessary to understand herbivory patterns in other parts of the plant. In agricultural systems, landscape structure is determinated by vegetation patches, crops and the movement of associated fauna. This study evaluated herbivory damage on potato leaves as a function of proximity to patches of native vegetation in the municipality of Combaya (La Paz, Bolivia). The percentage of leaf damage, damage level, leaf area and herbivore richness were measured in five potato crops. The results showed that close vegetation crops have significantly higher herbivory than far away ones (ANOVA P<0.00023729, F=9.3046). Close vegetation crops showed 8.266±0.859 % herbivory, while are away ones 5.909±0.585 %. In total, five morpho-species of herbivores were found associated with potato crops: 3 in crops near and 2 in crops far from the vegetation. The native vegetation plays an important role because it allows the fauna to take advantage of the resources of the entire landscape.